Pattern of colorectal cancers at tertiary rural hospital in Central India - Khachane, Tushar S.; Karandikar, Sangram (International Surgery Journal, 2021)
Background: In India the incidence of colorectal cancers is moderate to low but the five year survival of colorectal cancers in India is one of the lowest in the world. The poor survival rate warrants the assessment of reasons. Population based data is available only from few regions in India. Hospital based data may give a crude idea regarding the cancer distribution in the respective areas. Methods: The present study was carried out at a tertiary rural hospital in central India. A total of 216 cases of primary malignant tumors of colon and rectum presenting over a period of 10 year interval from 1994 to 2004 were analyzed for demographic and clinical presentation. ResultsThe peak incidence of cancer of colon and rectum was in 7th and 6th decade respectively. The M: F ratio was found to be 1.6: 1 for colorectal cancers combined. The mean age of presentation was 50.6 years. 25% patients with colorectal cancers were below age of 40 years. 48.3% patients with cancer of colon and 79.5% with cancer of rectum had locoregional disease, while 38.2% and 15.7% had distant spread respectively. Conclusions: Rectal cancer was found to be much commoner than colonic cancer supporting the case of independent etiologies. The incidence of colorectal cancer in young patients was high. Disease confined to the primary organ when the patient is first treated was very low.